2012
DOI: 10.1149/2.058211jes
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Phase Analysis in Sodium Metal Halide Batteries: Neutron Diffraction and Tomography

Abstract: Neutron methods are powerful tools for non-destructive investigation of batteries. Taking as an example the case study of a Fe/NaCl based battery, we investigate a discharged and a half-charged battery using spatially resolved neutron tomography and powder diffraction. Both batteries, the discharged and the half-charged, were studied by neutron tomography to identify the inner structure of the cells. The analysis of the neutron diffraction data allowed identification and quantification of the reaction zones as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Thanks to the selectivity of neutron diffraction data it is possible to study every single reaction that takes place inside the cell at the same time and the relationship between them, in time and space. The study is a basis for future improvements in the composition of the cathode through the optimization of the quantity of main components (NaCl, Fe, Ni) in order to increase the energy density of a sodium metal halide cell [53,54].…”
Section: Jdn 21mentioning
confidence: 99%
“…Thanks to the selectivity of neutron diffraction data it is possible to study every single reaction that takes place inside the cell at the same time and the relationship between them, in time and space. The study is a basis for future improvements in the composition of the cathode through the optimization of the quantity of main components (NaCl, Fe, Ni) in order to increase the energy density of a sodium metal halide cell [53,54].…”
Section: Jdn 21mentioning
confidence: 99%
“…From the tomography data initial information about the inner structure, porosity and the charge state of the respective batteries could be obtained (for more details see [10]). In the diffraction experiment we took advantage of the setup at the diffractometer STRESS-SPEC to investigate small volumes within bulky samples usually used for strain measurements.…”
Section: Spatial Resolved Phase Analysis In Battery Researchmentioning
confidence: 99%
“…The reaction front was identifi ed as the border between the FeCl 2 and the NaCl/Na 6 FeCl 8 phase, respectively, with its position being consistent with the tomography results. Add-on studies were recently successfully performed to follow the electrochemical process in-situ during charge and discharge, again taking advantage of the high fl ux of The measurement position is shown schematically as line in the horizontal image from the tomography data of the battery (see [10] for more details). STRESS-SPEC and the possibility to resolve and determine locally within the battery different crystallographic phases.…”
Section: Spatial Resolved Phase Analysis In Battery Researchmentioning
confidence: 99%
“…Our previous experiments showed that spatially resolved neutron diffraction can be used to map the phase distribution within a Na/FeCl 2 cell. 7 Because of their high penetration depth, neutrons are very well suited for non-destructive in situ measurements on the thick sodium metal halide cells and even allow to obtain crystallographic information on the phases by standard structure refinement techniques like the Rietveld method. 7 In the current study we have collected neutron diffraction data at several positions in the cathode of a sodium metal halide cell with mixed Fe/Ni chemistry during charge and discharge.…”
mentioning
confidence: 99%
“…7 Because of their high penetration depth, neutrons are very well suited for non-destructive in situ measurements on the thick sodium metal halide cells and even allow to obtain crystallographic information on the phases by standard structure refinement techniques like the Rietveld method. 7 In the current study we have collected neutron diffraction data at several positions in the cathode of a sodium metal halide cell with mixed Fe/Ni chemistry during charge and discharge. Since the reaction travels through the cathode of the cell during charge, looking at one fixed position in the cell only gives an incomplete picture of the processes in the cell, and collecting data at several positions with different distance to the ceramic separator is necessary to see how the reaction front propagates through the cell with time during charge.…”
mentioning
confidence: 99%